Environmental analysis (Scottish Historical and Archaeological Internet Reports, 2024)
An archaeological watching brief was undertaken at the Jedburgh Abbey Rampart during repair and construction works to consolidate and secure the ‘rampart’ wall and its face, both of which had begun to deteriorate and fail. The watching brief followed on from earlier works to investigate the construction of the ‘rampart’, which had revealed the presence of disarticulated skeletal remains behind the wall. The excavations undertaken during the repair works have helped to infer the methods employed for the construction of the ‘rampart’, likely dating to the late 18th century. During construction several burials of the former Low Kirkyard were disturbed and displaced, with the disarticulated remains of several skeletons found within the construction deposits. The watching brief also revealed the remains of five burials that were partially disturbed during construction, with skeletal remains dating from the 15th century onwards. Disturbance to earlier graves, not disturbed by the construction, were also identified, the results of which indicate changing attitudes to skeletal remains through the post medieval and early modern periods.